Practical tools for tracing P-V curves of Electrical Power Systems - Neto, Alfredo Bonini [UNESP]; dos Santos, Wesley Prado Leão [UNESP]; Alves, Dilson Amancio [UNESP]; Minussi, Carlos Roberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
This paper presents the features of proposed methods that allow the tracing of the P-V curves. With small modifications it becomes possible to use the traditional methods such as the Newton's method, that makes use of the Jacobian matrix, which becomes singular in the maximum loading point (nose point); and of the standard fast decoupled load flow (version XB and BX), believed not to be adapted for the computation of the points below and near the point of maximum loading. These methods are compared to each other with the purpose of pointing out its features. The results obtained for the IEEE systems (14, 30, 57 and 118 buses) are also compared with the ones of a continuation power flow method and of an optimal power flow. It was observed that in all the methods tested the maximum loading points found were always the same.
Keywords: continuation power flow; maximum loading point; P-V curves; voltage collapse